Induction of labor in Mid-Western Hospital in Nepal: Practice and Solution - Dhakal, Keshar Bahadur; Dhakal, S; Shrestha, S; Bhandari, S (Nepal Journal of Obstetrics and Gynaecology, 2018)
Introduction Induction of labour has been common intervention in modern obstetrics. This study is aimed to determine the distribution of practice and outcomes related to induction of labour in Mid-Western Regional Hospital in Nepal. Methods This is a retrospective cross-sectional study conducted at Mid-Western Regional Hospital in Surkhet, Nepal. Secondary data were collected from patients’ records of the hospital dating from 16 July 2016 to 15 July 2017. All women who underwent induction of labour with oral misoprostol were included in this study. For induction of labour, maximum five doses of 50 microgram oral misoprostol was administered in every four hours. Descriptive summary statistics such as frequency and percentages were calculated. Results Out of total 3,694 pregnant women who delivered in MWRH, 10.5% (n = 387) were induced by oral misoprostol. Majority of labour induced women were in the age group of 20 – 24 years (52.9%), 37 – 42 weeks of gestation (69.5%), and multi-gravida (49.9%). Majority (77.0%) who underwent induction of labour had vaginal delivery. Among total induction of labour, 88.9% had healthy babies. Majority of new borns had APGAR score of six or more in both one minute (87.9%) and five minutes (93.6%). More than half of the new borns (54.5%) had birth weight of 3000 – 3500 grams. Most of the induced cases (97.4%) were free of complications. Only 1.3% of cases had post-partum haemorrhage. Conclusions Induction of labour using oral misoprostol is a common practice in Mid-Western Regional hospital in Nepal and majority (77.0%) who underwent induction of labour had vaginal delivery.